More than 30 years after Malvinas; war in film and television - Savoini, Sandra (2017)
The Malvinas War of 1982 was the only Argentine war in the 20th century. It took a toll of 649 deaths in the area of operations and over a thousand wounded. Moreover, as estimated by veteran organizations, it led to the suicide of some 500 soldiers ?an approximation, as there is no official data? over the course of the 30 following years. The war was a breaking point not only for foreign policy, but also for domestic policy, as it precipitated the end of the military dictatorship.